Enhancing Teacher Competence in Deep Learning–Oriented Instructional Design: A ChatGPT–Supported Training at SMPN 5 Indralaya Utara in the Era of Artificial Intelligence - Ismet, Ismet; Ritonga, Ahmad Fitra; Pribadi, Imam Arif; Syamsudin, Frendi Ihwan (Unram Journal of Community Service, 2026)
The integration of Artificial Intelligence (AI) in education presents opportunities to enhance teacher competence and promote Deep Learning–oriented pedagogy. This study reports on a community service program conducted at SMP Negeri 5 Indralaya Utara, aimed at improving teachers’ skills in designing lesson plans that foster higher-order thinking and meaningful learning experiences with the support of ChatGPT. Ten teachers participated in a structured training program, which included pre-assessment, theoretical orientation, hands-on workshops, collaborative lesson plan development, mentoring, and post-assessment. Teachers’ understanding and application of Deep Learning principles were evaluated using pretest and posttest instruments, and the magnitude of improvement was measured using Normalized Gain (N-Gain). Results indicated an average N-Gain of 0.53, categorized as medium, demonstrating significant enhancement in formulating higher-order learning objectives, designing reflective and analytical activities, and utilizing AI to generate contextualized instructional materials. The findings highlight the effectiveness of practice-based, collaborative, and mentored training in improving both technological literacy and pedagogical skills. Moreover, teachers began transitioning from traditional knowledge-transfer approaches to constructivist, student-centered practices, positioning AI as a reflective pedagogical partner. This study provides evidence that structured professional development integrating AI can foster innovation, adaptability, and reflective instructional design, supporting Education 5.0 objectives and enhancing the quality of classroom learning experiences.